Policy Objective of Military Intervention and Public Attitudes: A Conjoint Experiment from US and Turkey - Osman Sabri Kiratli (Political Behavior, 2024)
This paper scrutinizes the role of the principal policy objective of military intervention in conditioning citizen attitudes for the use of force. Extending the scope of analysis beyond the independent effects, it next assesses how the effects of two core variables of intervention, namely international organizations' approval of the operation and the regime type of the target country, vary for interventions with differing mandates. The results of the conjoint experiment in two dissimilar cases, the US and Turkey, show that despite substantial changes in relative support for different types of operations, policy objective is still a highly potent determinant of individual attitudes. The results also concur that compared to foreign policy restraint and humanitarian missions, individuals are more sensitive to international organizations' endorsements of the use of force for peace and internal political change operations. Finally, individuals are significantly disapproving of operations that seek internal politic
https://doi.org/10.7910/DVN/TGUADW
Keywords: 320; Public Opinion; Conflict; Military Intervention; US; Turkey